Writing and speaking in the technology professions a practical guide - Beer, David F. (IEEE Press, 1992)
This book delivers concrete advice from foremost experts on how to communicate more effectively in the workplace. Beer includes discussions of a variety of approaches such as: writing technical documents that are clear and effective, giving oral presentations more confidently, presenting information visually through graphics, holding productive meetings, and becoming an effective listener.